Cytogenotoxic potential of Terminalia actinophylla (Mart.) bark in Allium cepa L. (Research, Society and Development, 2020)
Terminalia actinophylla (Mart), commonly known as "chapada", is used in folk medicine for the treatment of diarrhea, diabetes and anti-inflammatory. However, studies on its toxicity are still incipient. The present work was carried out with the objective of evaluating the phytochemical profile and the cytogenotoxic effect of the ethanolic extract of the T. actinophylla bark using the Allium cepa L. seed. Seeds of A. cepa were subjected to different extract concentrations (1.25, 2.5, 5 and 10 mg/mL), a negative control (NC - distilled water) as well as trifluralin (PC - positive control), during 24 h of exposure. The phytochemical profile of the extract was obtained to identify the main secondary metabolites. The cytotoxicity (mitotic index) and the genotoxicity (chromosomal alterations) were analyzed by means of the collection of 5,000 meristematic cells. The statistical analysis was carried out using the Kruskal-Wallis test (p